Pengembangan Corporate Storytelling Yayasan Grandma Foundation dalam Meningkatkan Awareness Publik - Dwi Ulina Sari; Mauly Arzak Julika (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to develop the communication strategy of Grandma Foundation through a corporate storytelling approach to enhance public awareness of its social programs. The main challenge faced by the foundation is the limited communication strategy, which has predominantly focused on informative reporting and has not yet effectively built emotional engagement with the public. The program employed interactive lectures, storytelling workshops, digital content production simulations, and mentoring and evaluation sessions. The results indicate a significant improvement in the foundation’s internal capacity to produce human-centered, authentic, and impact-oriented narratives. The implementation of corporate storytelling led to more consistent, emotionally engaging, and effective communication content, particularly through digital media. The discussion highlights that storytelling plays a strategic role in building public trust, strengthening organizational identity, and increasing public engagement. This program concludes that corporate storytelling is a relevant and effective communication strategy for nonprofit organizations to expand social impact and ensure the sustainability of their programs.